The Strong Male Dance Learning Evaluation at SMK Negeri 8 Surakarta in the Post-COVID-19 Pandemic - Chrisan Tiyansa; Usrek Tani Utina (Jurnal Seni Tari, 2023)
The COVID-19 pandemic has made learning online. Meanwhile, dance learning is more effective when implemented face-to-face. Therefore, the student's achievement in SMK Negeri 8 Surakarta decreased when learning online, especially in the Strong Male Dance subject. It happens because of the dominating women of the students. Therefore, after entering the post-pandemic period of COVID-19, there should be efforts to improve learning implemented face-to-face again, including the implementation of the evaluation because evaluation activities have an essential role in knowing the achievement of learning objectives. This study aims to understand, describe, and examine the implementation of the learning evaluation of the Strong Male Dance at SMK Negeri 8 Surakarta. This study used a qualitative method with the case study and pedagogic approaches with data collection techniques through observation, interviews, and documentation. Data validity techniques were tested again by theory, source, and technique triangulation. In addition, data analysis techniques used data reduction, data presentation, and data verification. The results show that the teachers provided additional learning media through video tutorials, PowerPoint materials, and the tolerated assessment criteria for female students. The existence of tolerance for assessment criteria increases in achieving the learning objectives and fosters the students' confidence. Hopefully, the results of this study can be used as literature to add knowledge to the evaluation of dance learning in the post-COVID-19 pandemic.